The Influence of Corporate Social Responsibility on Corporate Financial Performance in China - Liu, Shuai (2019)
Frequent outbreaks of sweatshops, consumer rights infringement, labour disputes, environmental pollution and other social problems, make corporate social responsibility has drawn more attention from the public. Undertaking CSR is beneficial for enterprises’ survival and development. With the progress of society, consumers pay more attention to the brand image of enterprises and the environment. They not only consider the products they purchase, but also care about the social responsibility of enterprises. The relationship between corporate social responsibility and financial performance has always been a popular topic among scholars. From the early shareholder value maximization theory to the current enterprise value maximization, the enterprise profit goal has changed from only protecting shareholders' income to realizing its own value and also realizing the social value maximization. However, due to different opinions on research methods and selection of indicator system, the relationship between CSR and CFP has not been concluded until now. In addition, the implementation of CSR in developing countries is obviously inferior to that in developed countries. Therefore, this paper takes Chinese industrial enterprises as the research object to study the relationship between CSR and CFP. This study is based on the stakeholder theory to explore the impact of corporate social responsibility on financial performance. Firstly, theoretical study on the meaning of CSR and related theories was carried out. Secondly, a series of quantitative analysis was carried out, including descriptive analysis, correlation analysis and regression analysis, and finally the following conclusions were drawn: Generally speaking, enterprises' assuming the responsibilities of various stakeholders has a significant promoting effect on the current and lag period of financial performance. To be specific, for sample enterprises, taking social responsibilities to shareholders and suppliers plays a very significant role in promoting financial performance. Undertaking social responsibility to employees and creditors has a fairly significant positive effect on corporate financial performance. In addition, the research results showed that there is no significant correlation between corporate responsibility to suppliers and financial performance, which is related to the fact that the sample enterprises pay insufficient attention to the interests of suppliers. This study also has some limitations. Firstly, the selection of research samples is not comprehensive enough, and the influence of some unlisted companies is ignored. In addition, other industries were not included in the study. In terms of research model, this study found that the index regression results of enterprises' responsibility to suppliers were not significant, which means that the variables selected in this study needed to be further improved.